Media Sosial, Pendidikan Kewirausahaan Berdampak terhadap Minat Berusaha Dimensi oleh Inovasi Mahasiswa di Cikarang - Prasetyo Harisandi; Fiqih Maria Rabiatul Hariroh; Etty Zuliawati Zed (STKIP PGRI SITUBONDO, 2023)
Abstract: The purpose of this study was to determine the effect of social media, entrepreneurship education and innovation on student interest in doing business in Cikarang. The method used in this research is descriptive method. The research method used in this research is descriptive quantitative. Quantitative descriptive data analysis was carried out using multiple linear regression analysis. Smart PLS (partial least squares). The basic population of this study were students in Cikarang, as many as 108 student respondents, which used a sampling technique in this study. So based on the results of the PLS test that has been done, it can be concluded that all the variable components of social media, entrepreneurship education and innovation have a significant positive influence on student interest in doing business in Cikarang. To deal with current changes, students must improve their abilities in learning online marketing so that they can do business so that they develop quickly and are known everywhere.